Menangkal Radikalisme Dengan Penguatan Pendidikan Karakter Nasionalisme Melalui Amaliyah Aswaja di SD Islamiyah Magetan - Irwan Fathurrochman; Abu Muslim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study explains how the implementation of strengthening nationalism character education and what factors influence the implementation of nationalism character with Aswaja amaliyah as counter radicalism in SD Islamiyah Magetan. Then what are the impacts on counter radicalism? All these questions will be answered by researchers using a qualitative approach. This research uses descriptive analytical thinking method with field research. The results of this study are that students are able to fortify themselves from the influence of radicalism that spreads in schools and schools. The inhibiting factor is the influence of social media which is often accessed by students from propaganda. Meanwhile, another supporting factor is the commitment to the parents of students through good communication towards understanding the importance of nationalism character education through Amaliah Aswaja. So that it is hoped that it can support nationalism character education through Amaliah Aswaja able to ward off radicalism.